Ovarian Cancer Methods and Protocols - Malek, Anastasia.; Malek, Anastasia.; Tchernitsa, Oleg.; Tchernitsa, Oleg. (Methods in Molecular Biology, 2013)
Ovarian cancer is the most lethal malignancy of the female reproductive system and is also the fifth leading cause of cancer death in women. Sharing common characteristics of cancer, ovarian malignancy possess several clinical and biological particularities  In Ovarian Cancer: Methods and Protocols, expert researchers in the field provide methods that have been created or adapted to study various aspects of ovarian cancer. These methods and techniques are applicable to study genetic alterations present in ovarian cancer, structural and metabolic features of ovarian cancer cells, include  in vitro and in vivo models that recapitulate ovarian cancer development and progression, and describe ovarian cancer-oriented drug delivery approaches. Methodological chapters are grouped into seven thematic parts, any of them is introduced by short subject review. Written in the highly successful Methods in Molecular Biology series format, chapters include introductions to their respective topics, lists of the necessary materials and reagents, step-by-step, readily reproducible laboratory protocols, and key tips on troubleshooting and avoiding known pitfalls.     Authoritative and practical, Ovarian Cancer: Methods and Protocols seeks to aid scientist to optimize study designs, to correctly select the most applicable methods, and to produce interesting and novel results.